2004
DOI: 10.1186/1476-5926-2-s1-s12
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin receptors in hepatic sinusoidal cells

Abstract: Emerging evidence has suggested a critical role of leptin in hepatic inflammation and fibrogenesis, however, the precise mechanisms underlying the profibrogenic action of leptin in the liver has not been well elucidated. Therefore, the present study was designed to investigate the expression and functions of leptin receptors (Ob-R) in hepatic sinusoidal cells. Hepatic stellate cells (HSCs), Kupffer cells and sinusoidal endothelial cells (SECs) were isolated from rat livers by in situ collagenase perfusion foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…1). These findings are consistent with findings that have been reported by other groups (8,26,27) and suggest that leptin signaling activity might increase during HSC transdifferentiation, despite associated repression of leptin receptor mRNAs. To further evaluate leptin receptor function in MF-HSCs, day 7 cultures of MF-HSCs were treated with exogenous leptin, and effects on HSC gene expression were assessed by qRT-PCR.…”
Section: Leptin (Ob)/ob Receptor Interactions Differentially Modulatesupporting
confidence: 83%
See 1 more Smart Citation
“…1). These findings are consistent with findings that have been reported by other groups (8,26,27) and suggest that leptin signaling activity might increase during HSC transdifferentiation, despite associated repression of leptin receptor mRNAs. To further evaluate leptin receptor function in MF-HSCs, day 7 cultures of MF-HSCs were treated with exogenous leptin, and effects on HSC gene expression were assessed by qRT-PCR.…”
Section: Leptin (Ob)/ob Receptor Interactions Differentially Modulatesupporting
confidence: 83%
“…Evidence that treating HSCs with siRNA to knock down expression of leptin significantly inhibited the myofibroblastic phenotype of cultured HSCs (34) supported this concept. Other reports, however, failed to demonstrate such leptin-dependent effects when HSCs were cultured in serumenriched medium (27,35), prompting speculation that leptin was neither necessary nor sufficient for HSC activation and leaving lingering questions about the ultimate significance of leptin-HSC interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We then performed gene expression analysis of FACS-sorted VE-cadherin + PTN + cells, which revealed enrichment for VEGFR2 and VEGFR3, which are markers of BM sinusoidal endothelium (Hooper et al, 2009)(Table 1). Interestingly, VE-cadherin + PTN + cells were also enriched for expression of CXCL12 and the leptin receptor (lepR), proteins which have been shown to be expressed by both perivascular stromal cells and sinusoidal ECs (Dar et al, 2005; Ding et al, 2012; Ikejima et al, 2004; Sugiyama et al, 2006). VEcadherin + PTN + cells lacked expression of Nestin, a marker of BM mesenchymal stromal cells (MSCs) (Mendez-Ferrer et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrate via immunohistochemical and FACS analysis that PTN is expressed uniquely by VE-cadherin + ECs that co-express VEGFR2 and VEGFR3 + , consistent with BM sinusoidal ECs (Hooper et al, 2009). Interestingly, PTN + ECs also express CXCL12 and lepR, which can be expressed by both sinusoidal ECs and perivascular reticular cells (Dar et al, 2005; Ding et al, 2012; Ikejima et al, 2004; Sugiyama et al, 2006). Of note, a prior study suggested that calvarial bone osteoblasts expressed PTN (Tezuka et al, 1990), but we found little evidence that osterix + bone lineage cells expressed PTN in the BM.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin levels are elevated in obese adults [80], indicating a resistance to the effects of leptin in these individuals [81]. Recent reports have suggested that leptin is involved in wound repair and fibrosis [82][83][84][85]. Irrespective of the organ, wound repair involves integrated and balanced cell proliferation, angiogenesis, and extracellular matrix production.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%